Cellular therapies for the treatment of non-union: The past, present and future - Homma, Yasuhiro; Zimmermann, Gerald; Hernigou, Philippe (Injury, 2013)
Non-union fracture is a pathological condition having some impairment of the cellular part of the repair: a reduction of MSC and of the osteoblastic activation. Non union is therefore a good indication for cell-based therapies using stem cells. We described the rational of this treatment and described the technique of autologous bone marrow concentrate implantation that was until now used. With the development of stem cell research and regenerative medicine, we believed that therapy based on cytotherapy has great potential. In this review, clinical applications of cytotherapy are summarized and analyzed. Current problems and future challenges are discussed.